Poster: We Are Well: Well-being superpowers - portraits of well-being - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
The poster, ‘We Are Well: Well-being superpowers- portraits of well-being’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. The poster showcases drawings of our well-being superpowers alongside our portraits. Poster text: We are creating well-being portraits together as we mentor each other. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Nikki Browne, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.